Return to Zion addresses on religious Zionism and american orthodoxy - Soloṿeyṭshiḳ, Yosef Dov 1903-1993 (OU Press, 2023)
"Rabbi Joseph B. Soloveitchik (known simply as "the Rav") was the Torah giant of the last century long aliated with Religious Zionism. His addresses delivered at major conferences and conventions of Mizrachi Organization of America and Hapoel Hamizrachi of America were the high point of these gatherings, as the Rav mesmerized his audience with perceptive observations on the state of American and Israeli Jewry as well as the nature of Religious Zionism. is book contains ten of those discourses, translated from the original Yiddish, delivered by the Rav between 1939 and 1958 against the backdrop of the Holocaust and the newly-emerging State of Israel. e Rav’s stirring and profound words from one of most challenging periods in Jewish history are timeless and powerful messages of the unending drama of Jewish destiny. FROM THE RETURN TO ZION: In my opinion, it is here that the religious conception of the ideology of the return to Zion lies hidden. I do not refer simply to the mitzvah to settle the land or to other mitzvot connected with the land. Much more depends on this: the entire character of Judaism and its essence. Will Judaism remain a unidimensional line or a twodimensional plane, or will it be transformed into an all-encompassing space – long, wide, and deep, with distant horizons and unending boundaries – in a word: a true worldview? I believe that, even with the best of intentions, Diaspora Jewry cannot accomplish this. Observance can exist but not a multidimensional Jewish society. is is not simply some abstract reection but an actual necessity if we expect that out of Gehenna will emerge a new Jewish persona with a new view of life, a new system of values, who will make the great paradox of Abraham’s covenantal vision, of Moses’ "e Lord! the Lord! a God compassionate and gracious," a reality; who will bring us both into contact with world culture and into tension with it [...]."
Translation into English
Keywords: Geschichte 1939-1967; Orthodoxes Judentum; Zionismus; USA; Aufsatzsammlung